Comprehensive assessment of the acute lethal, risk level, and sub-lethal effects of four insecticides on Trichogramma ostriniae - Wenya Zhu; Qiongqiong Guo; MengJiao Chen; Juan Wang; Ye Zhang; Ruiyan Ma (PLoS ONE, 2025)
Trichogramma ostriniae is one of the most successfully used natural enemies in the integrated management of agroforestry pests. However, the extensive use of insecticides poses a significant threat to the survival and efficacy of T. ostriniae. To assess the compatibility of chemical pesticides with T. ostriniae, we investigated the acute toxicity, risk level, and sub-lethal effects of four insecticides (chlorfenapyr, emamectin benzoate, phoxim, and lambda-cyhalothrin) on reproduction, parasitism, detoxification enzymes, protective enzyme activities, and active substances under laboratory conditions. The results revealed that phoxim had the highest acute toxicity, with a median lethal concentration value of 2.8 × 10−7 mg/mL, whereas chlorfenapyr had the lowest at 5.06 × 10−3 mg/mL. Emamectin benzoate was classified as high risk, whereas the others were classified as extremely high risk. Insecticide exposure during the larval and pupal stages significantly reduced the emergence of T. ostriniae (P < 0.05). Lambda-cyhalothrin, emamectin benzoate, and chlorfenapyr extended the time required for prey-handling and reduced parasitism efficiency by 0.70%, 2.45%, and 4.50%. In contrast, phoxim increased the time required for prey-handling and improved parasitism efficiency by 25.37%. All insecticides affected protective enzyme activities, induced detoxification enzyme activity, reactive oxygen species, malondialdehyde and mitochondrial respiratory chain complex I levels, and decreased the adenosine triphosphate level. These findings underscore the differential impacts of insecticides on T. ostriniae and emphasize the need for cautious pesticide selection to balance pest control and natural enemy conservation, providing essential scientific guidance for sustainable agroforestry pest management.